Use Pattern of Smartphone on Young People, Blessings and Risks (Journal of Dhaka National Medical College & Hospital, 2020)
Introduction: This paper presented a study on trends in smartphone usages among the young people in Dhaka city. This research provided various purposes of using cell phone and access internet on distinct ways.Objective: This study was undertaken to compare socio economic characteristics, purposes, behavioral changes, commonly using applications and problems arising from using smartphone. Methodology: This study was done in some selected area of Dhaka city from February 2019 to February 2020. A cross sectional design was used to collect data from 1000 respondents with the specific age group ranging from 15 to 40 and convenient type of non-probability sampling was used as a sampling technique. Data analysis was done by the computer with the help of SPSS 22 programme.Result and Discussion: About 79.8% of young people use smartphone for communication, whereas 69.1% for watching videos. Maximum users of smartphone are students. For this excessive use of smartphone they faced some problems such 22% are complaining headache, 27.3% for eye pain andso on.Conclusion: Results revealed health issues most significantly eye pain, neck pain and headache. Further it showed not only the merits of smartphone but also some demerits of excessive use of it.J. Dhaka National Med. Coll. Hos. 2020; 26 (01): 16-20